A review and synthesis of research on comprehension of the masculine as a generic form in English - Henley, Nancy M; Abueg, Joselito (Sociolinguistic Studies, 2003)
In this article we survey studies providing empirical tests of questions related to the comprehension of masculine generics; these are categorized by experimental paradigm. Findings are aggregated and weighted Stouffer combined tests are performed to assess the probabilities of the findings across studies. The evidence indicates that not only are masculine forms more likely to lead to male-oriented than to other responses, but also that this tendency is strongly evidenced in both children and adults, and that females are more likely than males to interpret masculine forms generically (p .00001 for each combined test). The evidence is mixed on whether sex-neutral or sex-inclusive forms provoke more generic interpretation, but may favor the inclusive forms. Many children, and 10% or more of adults tested, were unable to explain the masculine generic rule satisfactorily. Processing time studies indicate that a male-related response is more cognitively available than other responses following a masculine generic antecedent. Finally, there is a residual tendency to make male-oriented responses regardless of the stimulus.